Perioperative Management in Patients with Temporary Pacemaker Who Underwent Craniotomy in Prone Position - Purwoko; Handayu Ganitafuri (HM Publisher, 2022)
Introduction: As the incidence of the need for a pacemaker increases, an anesthesiologist may encounter patients with pacemakers who need surgery other than the heart. With enough knowledge, the outcome of patients with pacemakers undergoing procedures other than cardiac surgery can be optimized with the hope that mortality and morbidity can be avoided. Case presentation: Male, 42 years old, with Temporary Pacemaker (TPM), programmed for evacuation craniotomy and decompression. The patient had Intracranial Hemorrhage (ICH) after the Percutaneous Intra Arterial Thrombolysis (PIAT) procedure 2 days earlier. The patient was stable during the operation, which lasted for 3 hours in the prone position. Conclusion: The perioperative strategy should be customized based on the procedure, the needs and values of the patient, and the device attached. The primary focus of perioperative management in patients who underwent surgery is minimizing the possibility of electromagnetic interference (EMI).